Embeddedness of regions in European knowledge networks. A comparative analysis of inter-regional R and D collaborations, co-patents and co-publications - Iris Wanzenböck; Thomas Scherngell; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2013)
This paper investigates the embeddedness of European regions in different types of inter-regional knowledge networks, namely project based R and D collaborations within the EU Framework Programmes (FPs), co-patent networks and co-publication networks. Embeddedness refers to the network positioning of regions captured in terms of social network analytic (SNA) centrality measures. The objective is to estimate how region-internal and region-external factors influence network embeddedness in the distinct network types, in order to identify differences in their driving factors at the regional level. In our modelling approach, we apply advanced spatial econometric techniques by means of a mixed effects panel version of the Spatial Durbin Model (SDM), and introduce a set of variables accounting for a capacity-specific, a relational as well as a spatial dimension in regional knowledge production activities. The results reveal conspicuous differences between the knowledge networks. Internal capacity- and technology-related aspects but also spatial spillover impacts from surrounding regions prove to be particularly important for centrality in the co-patent network. We also find significant - region-internal and region-external - impacts of general economic conditions on a region's centrality in the FP network. However, we cannot observe substantial spill-over effects of region-external factors on centrality in the co-publication network. Thus, the distinctive knowledge creation foci in each network seem to find expression in the network structure as well as its regional determinants.
Keywords: L14; N74; O33; R15; 330; knowledge networks; network embeddedness; network centrality; regional knowledge production; panel Spatial Durbin model